Little Hands in Harmony: Pendampingan Siswa dalam Meningkatkan Antusiasme terhadap Seni Karawitan di SDN Sahang, Kecamatan Ngebel, Kabupaten Ponorogo - Vivin Hidayah; Nafi'ah (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Karawitan is a traditional Javanese art that holds great importance in cultural preservation. However, at SDN Sahang Ngebel Ponorogo, student interest in joining karawitan extracurricular activities remains low, as many prefer other activities they find more appealing. The current teaching methods are also considered monotonous, leading to boredom and a lack of enthusiasm. In fact, karawitan is not only a musical art form but also a medium to instill cultural values, discipline, and togetherness. Through community service activities, student mentoring was carried out with two main roles: motivator and creative facilitator. As a motivator, the program aimed to boost students’ enthusiasm by providing encouragement, guidance, and appreciation so they could feel more confident and proud to take part in karawitan. Students were also made aware that karawitan is not just an extracurricular activity, but also an effort to preserve regional cultural heritage. As a creative facilitator, learning was designed to be more enjoyable using a play-based approach, such as guessing instrument sounds, rhythm relays, and introducing traditional songs accompanied by gamelan music. This approach made students feel happier, more engaged, and less bored during practice. As a result, their enthusiasm and participation increased significantly. Students who were previously uninterested became more active, gained confidence in playing instruments, and felt proud to contribute to preserving gamelan music. This program successfully fostered students’ appreciation of traditional arts while supporting cultural preservation at school.